Green Protectionism Or Green Diplomacy: An Analysis Of Indonesia’s Response To The Implementation Of The EU CBAM - Puan Putri Muthia; Muhammad Farid; Syafhendry Syafhendry (Jurnal Dinamika Global, 2026)
The European Union’s Carbon Border Adjustment Mechanism (CBAM) is a global climate policy aimed at preventing carbon leakage through the imposition of carbon tariffs on high-emission imports. This policy has generated debate, particularly among developing countries such as Indonesia, where it is often perceived as a form of green protectionism that may reduce the competitiveness of carbon-intensive export sectors. While previous studies have primarily focused on the economic impacts of CBAM, limited attention has been given to Indonesia’s strategic response from the perspective of environmental diplomacy. This study aims to analyze Indonesia’s response to the implementation of CBAM and assess whether the policy reflects green protectionism or creates opportunities for strengthening green diplomacy. Using a qualitative policy analysis based on thematic content analysis of official documents and relevant literature, this study employs structuralist and liberal perspectives to examine the policy dynamics. The findings indicate that CBAM has an ambivalent character: it reinforces structural inequalities through environmental trade barriers while simultaneously encouraging Indonesia to strengthen emission regulations, promote green industrial transformation, and enhance diplomatic engagement through mechanisms such as IEU-CEPA negotiations. This study contributes to the CBAM literature by demonstrating that the policy functions not only as a trade instrument but also as a catalyst for green diplomacy in developing countries.